Aggression as a contributing factor to social defeat and stress vulnerability - Megan M. John; Melissa A. Pratt; Jazmine D.W. Yaeger; Renée A. Brummels; Leighton J. Ledesma; Lauren S. Meyer; RaeAnn L. Hartwig; Gabriel L. Legner; Nathan G. Gilbertson; Patrick J. Ronan; Cliff H. Summers (Neurobiology of Stress)
The Stress Alternatives Model (SAM) is a social defeat/avoidance paradigm developed in our lab that reveals evolutionarily conserved escape responses in fish, hamsters, rats, and mice. During social interactions in a neutral arena, available escape routes sized exclusively for smaller test animals allow for avoidance of a social aggressor. This 4-day social interaction protocol pairs C57BL/6N test mice and a larger, novel, aggressive CD1 mouse each day. Although escape portals are available, and the CD1 aggressor is unremittingly antagonistic, only half of the mice tested utilize the escape tunnels, while escape latency dramatically decreases over time in mice that escape. We sought to determine whether aggression provided the trigger of two stress-related phenotypes that are produced by the SAM. The results suggest threat of aggression, determined by the first attack, is necessary for phenotype development, but the intensity of aggression over time does not determine which phenotype is chosen. Phenotypes are determined by responsiveness and counterbalanced neurocircuits that promote stress-resilience or vulnerability. These stress neurocircuits are modulated by orexins, through orexin 1 and 2 receptors (Orx1, Orx2), which promote pro-stress behaviors. In the primary pro-stress neurocircuitry of the aBLA, we examined Akt and mToR gene expression in stress-resilient (Escape) and -vulnerable (Stay) mice. The quantity of Hcrtr1 mRNA/cell was elevated in Stay mice, as were the mRNA/cell numbers for Mtor. However, the increase of Akt2 and Mtor mRNA/cell was not evident specifically in Hcrtr1 expressing cells, suggesting these molecular markers of neuroplasticity are not being activated by Orx1 receptors.